2017
DOI: 10.1080/15226514.2017.1319330
|View full text |Cite
|
Sign up to set email alerts
|

Influence of groundwater and wastewater irrigation on lead accumulation in soil and vegetables: Implications for health risk assessment and phytoremediation

Abstract: The current study evaluated the effect of groundwater and wastewater irrigation on lead (Pb) accumulation in soil and vegetables, and its associated health implications. A pot experiment was conducted in which spinach (Spinacia oleracea), radish (Raphanus sativus), and cauliflower (Brassica oleracea) were irrigated with groundwater and wastewaters containing varying concentrations of Pb. Lead contents were measured in wastewaters, soils and root and shoot of vegetables. We also measured health risk index (HRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 28 publications
0
50
0
Order By: Relevance
“…Soil pH is considered a master/key variable governing the chemical speciation of metals in soil [ 98 , 99 , 100 ]. It has been reported that the biogeochemical behavior of As in the soil–plant system mainly depends on soil pH [ 2 ].…”
Section: Speciation Of Arsenic In Soilmentioning
confidence: 99%
“…Soil pH is considered a master/key variable governing the chemical speciation of metals in soil [ 98 , 99 , 100 ]. It has been reported that the biogeochemical behavior of As in the soil–plant system mainly depends on soil pH [ 2 ].…”
Section: Speciation Of Arsenic In Soilmentioning
confidence: 99%
“…In the areas where fresh water is in short supply, wastewater is frequently used for crop irrigation. Although not legally permitted in most countries, the use of untreated wastewater for crop irrigation has been practiced in many countries worldwide due to the shortage of good quality water [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tannery wastewater contains several organic and inorganic pollutants [2]. Farmers mostly use tannery wastewater in periurban areas due to a scarcity of irrigation water [3,4]. There are different heavy metals in tannery wastewater, such as Cr, Cd, Mn, Pb, Fe, Ni, and Cu.…”
Section: Introductionmentioning
confidence: 99%